Pengaruh Budaya Nasrani terhadap Diskriminasi Kelompok Queer dalam Islam - Ersa Elfira Khaiya; Ferdiansah (Aqwal: Journal of Qur'an and Hadis Studies, 2023)
Discrimination against the Queer community within the Muslim community is often rooted in religious reasons. Some Muslims perceive Queer individuals as deviant, sinful, and divergent from Islamic Sharia. This is attributed to the numerous misinterpretations of the story of Prophet Lut in the Quran and hadiths, which are used to justify the discrimination against the Queer community. However, contemporary interpretations of the story of Lut are often overlooked in discussions regarding the context of why Allah sent punishment upon the people of Lut. Two fundamental questions underlie this research. First, what is the origin of the emergence of discriminatory rhetoric against the Queer community in the story of Prophet Lut in the Quran? Second, are there other influences that support such discrimination? The author finds that interpretations of the story of Prophet Lut are not singular, and there are other factors influencing the perpetuation of discrimination against the Queer community in Islam. This is due to the influence of pre-Islamic cultural attitudes towards Queer discrimination. There are verses in the Gospel that explicitly outline punishments for homosexuality, and it is believed that there is an overlap in understanding between Islamic and pre-Islamic (in this case, Christian) cultures in the construction of the narrative of the story of Prophet Lut.